PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN CV MANDIRI BAJA MULIA MELALUI MOTIVASI KARYAWAN SEBAGAI VARIABEL INTERVENING - Adella Novita Candra; Christian Herdinata (Politeknik Negeri Lhokseumawe, 2022)
Abstract: This study aims to analyze the effect of leadership and compensation on employee performance with motivation as an intervening variable at CV. Mandiri Baja Mulia In this study there were four variables, namely Leadership (X1), Compensation (X2), Motivation (Z), and Employee Performance (Y). The sample in this study was 50 employees of CV. Noble Steel Mandiri. The data analysis technique used is Partial Least Square Structural Equation Model with the help of SmartPLS version 3.0 software. Data collection techniques with questionnaires. The results of this study indicate that 1.) leadership has no significant effect on motivation, 2.) leadership has a significant effect on employee performance, 3.) compensation has a significant effect on motivation, 4.) compensation has no significant effect on employee performance, 5.) motivation significant effect on employee performance, and 6.) motivation does not have a mediating role in this study.Keywords : Leadership, compensation, motivation, employee performance